INSECTS IN THE COMMODITIES STORED IN THE ABIDJAN PORT AUTHORITY AND THE RISKS OF ACCIDENTAL INTRODUCTION OF NEW SPECIES IN COTE D’IVOIRE - Cecile, Sadia-Kacou Ayemou Manafoua; Jean-Pierre, Boga; Felicia, Johnson; Mauricette, Ouali-N’goran San-Whouli; Kouahou, Foua-Bi (European Scientific Journal, ESJ, 2015)
The inventory and the identification of the insects in the commodities stocked at the abidjan port authority (apa), one of the most popular in west africa, have been carried out in order to know the flow of insect fauna in the inbound and outbound farm products. Three (3) kilogramme samples have been selected and kept in polypropylene bags and labelled. In order to identify the insects, the selected sample has been poured into a sieve exposed to a 100 watt lamp to incite the insect to come out of the grains. The insects have been selected and examined by means of a magnifying glass in the insectary of the laboratory of zoology and animal biology of félix houphouët-boigny university. Overall, 924 insects were inventoried. They were of three natures (coleoptera, lepidoptera and heteroptera). The coleoptera were 985 individuals; they are predominant with 11 families encompassing 15 species. The lepidoptera that have been listed represent 18 individuals and grouped into 2 families and consist of 3 species. Then, the heteroptera composed of 33 individuals within the same family and represented by only one species. At the export, a total of 924 have been recorded with a slight predominance of coleoptera (95.1%), followed by the heteroptera (3.1%) then the lepidoptera (1.7%). By the time of export, the proportion of coleoptera recorded was 91.04%. The insects in all the inbound commodities such as s. Ozyzae (linné) curculionidae, s. Zeamais (motchulsky) curculionidae, s. Cerealella (oliver) gelechiidae, p. Flavipes (review) anthocoridae, have been noted, thus confirming the potential risks of introducing new species in the commercial exchanges.